Using video for microanalysis of teachers' embodied pedagogical practices. (September 2015) - Tobin, Joseph; Hayashi, Akiko
This paper briefly reviews theories of embodiment and then provides an example from our recent work on how we use video in our comparative studies of preschools to highlight embodied and implicit cultural pedagogies. The example we present focuses on how Japanese preschool teachers use the Japanese cultural practice of mimamoru (teaching by watching and waiting) as an embodied technique that combines gaze, location, posture, and touch. We demonstrate how a microanalysis of video footage, when used in conjunction with ethnographic interviews, can draw attention to culturally patterned embodied practices that may otherwise be difficult to perceive.